Peningkatan Prestasi Belajar Pendidikan Jasmani Olah Raga Kesehatan pada Materi Makanan Bergizi melalui Alat Peraga Gambar di Kelas II SDN Sejati 6 Kecamatan Camplong Kabupaten Sampang Tahun Pelajaran 2018/2019 - Suadi Suadi (Departement of Mathematics Education, 2023)
Media or educational media is commonly referred to as Audio Visual Aids (AVA). Audio means hearing, visual means seeing while aids means tools. Thus AVA is the same as a tool used in the learning process to facilitate the process of understanding concepts in students (Sahertian, 2006: 200). The purpose of this study in general was to get an overall picture of the activities to improve skills in solving fraction problems in Physical Education subjects in class II semester 1 UPTD SDN Sejati 6 Camplong District, Sampang Regency using visual aids. The use of picture teaching aids as learning media can improve student achievement in Physical Education subjects, especially in the subject of nutritious food in second semester 1st graders of UPTD SDN Sejati 6 Camplong District, Sampang Regency, which was marked by an increase in the value of learning outcomes that were originally 61.9 increased to 68.9 in the implementation of the improvement cycle I and 77.4 in the implementation of the improvement in the second cycle and the percentage of success from 30% before implementing the learning improvement to 45% in the improvement in the first cycle and 95% in the improvement in the second cycle